2017
DOI: 10.1002/chem.201700848
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Exfoliated Metal‐Organic Nanosheets through Hydrolytic Unfolding of Metal‐Organic Polyhedra

Abstract: Few-layers thick metal-organic nanosheets have been synthesized using water-assisted solid-state transformation through a combined top-down and bottom-up approach. The metal-organic polyhedra (MOPs) convert into metal-organic frameworks (MOFs) which subsequently self-exfoliate into few-layered metal-organic nanosheets. These MOP crystals experience a hydrophobicity gradient with the inner surface during contact with water because of the existence of hydrophobic spikes on their outer surface. When the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…However, significant recent work has shown that post‐synthetic stabilization strategies can successfully be employed for POCs [62, 63] where, for example, imine cages are transformed into highly stable amide or carbamate cages. Similarly, the development of paddlewheel‐based permanently porous coordination cages, which are hydrolytically unstable when built from copper clusters, [64] have shown excellent water stability when alternative metal cations are targeted [65] …”
Section: Introductionmentioning
confidence: 99%
“…However, significant recent work has shown that post‐synthetic stabilization strategies can successfully be employed for POCs [62, 63] where, for example, imine cages are transformed into highly stable amide or carbamate cages. Similarly, the development of paddlewheel‐based permanently porous coordination cages, which are hydrolytically unstable when built from copper clusters, [64] have shown excellent water stability when alternative metal cations are targeted [65] …”
Section: Introductionmentioning
confidence: 99%
“…Banerjee and coworkers demonstrated a transformative hydrolytic process from metal-organic polyhedra to layered MOF, which resulted in a spontaneous exfoliation to nanosheets of 6-8 layers thick upon addition of larger relative amounts of water. 39 Similarly, Gallego et al found that exposure of bulk layered crystals to excess water induced layer separation down to monolayer thickness, without any additional energetic input (Fig. 4l).…”
Section: Exfoliating Layered Mofsmentioning
confidence: 68%
“…The archetypal MOF-2 was amongst the rst layered MOFs to be exfoliated to form MONs and consists of layers of 1,4-benzene dicarboxylate (BDC) coordinated via Zn paddlewheels with water molecules occupying the axial positions of the paddlewheel. 35 Isostructural MONs have since been formed using a variety of metal ions (Cu, Zn, Co) and 1,4-BDC [36][37][38] and 1,3-BDC derivatives, [39][40][41] as well as longer linear diacid chains. 42 In our own work, we functionalised 1,4-BDC with weakly interacting alkylether chains designed to weaken interlayer interactions and aid exfoliation into solvent (Fig.…”
Section: Carboxylate Based Monsmentioning
confidence: 99%
“…[18]. This work presents the 13 C MAS NMR spectra of a series of Cu(II) isophthalate MOFs [5,19,20] and investigates the sensitivity of 13 C NMR spectroscopy to substitutions on the 5 position of the linker. It is also demonstrated that, although less ordered, the structure of dehydrated STAM-1 is very similar to that of dehydrated STAM-17-OEt on the local scale, confirming that this archetypal MOF also exhibits this interesting "crumple zone" response.…”
Section: Introductionmentioning
confidence: 99%